(untitled) (Politeja, 2021)
Following the idea of the “other” in the work of Ernesto Laclau and the perspective of post-foundational discourse analysis, the study focusses on Chinese strategical internal and external pre- and post-Covid-19 political specifics and policies and how they interact (or contradict) with the “European” vision of the world and most importantly itself. As Laclau says, “the notion of “constitutive outside” emphasizes the always present possibility that differential relationship between an entity and its “constitutive outside” turns into antagonism.” For more than three decades, the EC/EU has been steadily building up its foreign relations architecture and has proven its desire to project its ideals and values worldwide. However, during the same period, after “the century of humiliation,” China has also reached a point in its history where it wants to see the world according to its national interests and views. This work attempts to analyze some key features inherent to both the EU and China, such as strategies, relation with other countries, typical governmental architecture, and some aspects of identity, which could help in better understanding the possible contradictions and areas of cooperation in their way of conceptualizing themselves as key players on the world stage. This will reflect the need for greater European civic awareness in the upcoming decades, as suggested by the author.